IDENTIFIKASI TENUN CAGCAG KHAS BALI AGE DI DESA SEMBIRAN - Wende, Yohana (Universitas Pendidikan Ganesha, 2023)
Abstract The objective of this study is to provide a description of three main aspects: 1) the production process of cag-cag woven cloth, 2) the motifs used in cag-cag woven cloth, and 3) the sustainability of cag-cag woven cloth specific to Sembiran Village. This research adopts a qualitative descriptive research approach, utilizing observation and interview methods. The researcher acted as the instrument, employing observation sheets and conducting interviews. Descriptive analysis was employed to analyze the collected data. The findings of this study reveal the following: 1) The weaving process consists of five stages, namely: a) ngelinying, b) singing, c) injection, d) nyasah/saksah, and e) weaving. 2) Cag-cag weaving incorporates geometric motifs such as poleng and stripes. 3) Traditional looms are still used in the ongoing production of cag-cag weaving, preserving motifs passed down through generations. Synthetic dyes are utilized for yarn dyeing, and digital promotional channels have not been adopted yet.